Subcutaneous foslevodopa in akinetic crisis. A case report from the neurological intensive care unit - Loeffler, Moritz A.; Mengel, Annerose; Single, Constanze; Weiss, Daniel; Feil, Katharina (Frontiers in Medicine, 2024)
Akinetic crisis is a severe deterioration of motor performance occurring in syndromes with pre-or postsynaptic dopaminergic deficit, necessitating effective dopamine replacement therapy. The subcutaneously applicable levodopa derivative foslevodopa represents a new therapeutic option for patients with advanced Parkinson's disease as a continuous therapy. Its role as a parenteral treatment option for akinetic crisis has not been investigated, yet. A 78-year-old patient who had developed akinetic-rigid symptomatology in the context of normal pressure hydrocephalus was admitted to our intensive care unit after experiencing an acute exacerbation of akinesia in the context of pulmonary infection. Off-label administration of subcutaneous foslevodopa was initiated after repeated failures to insert a gastric tube for enteral application of levodopa and contraindications against amantadine and apomorphine. Following the administration of a subcutaneous test dose, continuous application of foslevodopa via a B. Braun syringe pump was gradually increased to 0.3ml/h during the daytime and 0.15ml/h at night, corresponding to a levodopa equivalent dosage of 1020mg/d. This was accompanied by an improvement of the MDS-UPDRS-III score from 85points to 59points after 72h. Treatment of an akinetic crisis with subcutaneous foslevodopa in an intensive care unit setting has proven safe and effective in a patient with acute akinesia associated with dopamine-sensitive hydrocephalus. Due to the pathophysiological distinction from Parkinson's disease, there may be differences in therapeutic response and side effects. Nevertheless, the method used here can serve as a protocol basis for the treatment of akinetic crises with foslevodopa in general and as a starting point for further research.